Clinical evaluation of paraspinal mini-tubular technique vs. laminoplasty for spinal intradural extramedullary tumors: Study protocol for a multicenter, randomized controlled trial - Wang, Rui; Liang, Ze-Yan; Chen, Yan; Chen, Chun-Mei (Frontiers in Surgery, 2023)
Abstract The development of minimally invasive surgery has promoted the use of the paraspinal mini-tubular technique (PMTT) for spinal tumors. The similarity of the efficacy of PMTT to that of traditional surgery remains unclear; randomized controlled trials (RCTs) have not been conducted to investigate this technique for spinal tumors. The conventional surgery used for such tumors is laminoplasty (LP). To compare the differences between the two surgical techniques, an RCT is significantly required. Therefore, a prospective, multi-center, non-inferiority RCT was designed to compare the safety and effectiveness of LP and PMTT for treating spinal intradural extramedullary (IDEM) tumors. Moreover, the availability of PMTT, including its advantages and disadvantages, surgical indications, procedures, complications, and prognosis, would be explored. Overall, 280 patients will be randomly allocated to the PMTT and LP groups in a 1:1 ratio. The trial hypothesis is that PMTT has superior or equivalent efficacy and cost-effectiveness to LP. The primary outcome is the Japanese Orthopedic Association score. The non-inferiority margin for the primary outcome is five. The Ethics Committee of Fujian Medical University Union Hospital, Fuzhou, China, has approved this study (project number: FJMUUH05). Any results of the trial will be published in international peer-reviewed journals and disseminated through presentations at scientific conferences. Trial registration number: ChiCTR2100047582